The effect of sustained VDU and Non-VDU nearwork on visual acuity and refractive error in emmetropic primary schoolchildren - Swee Chai, Teoh; Ai-Hong, Chen; Mohidin, Norhani (Scandinavian Journal of Optometry and Visual Science, 2012)
Myopic shift in refraction following a sustained period of near-work is well documented among adult visual display unit (VDU) users. This crossover study investigates the effect of VDU near-work on visual acuity and refractive status among 7-year-old children. Thirty emmetropic and low-hyperopic schoolchildren (refractive error: -0.25DS to +1.25DS, astigmatism ≤ 1.00DC and anisometropia ≤ 1.00D) participated in this study. All subjects (15 males and 15 females) were involved in two 2-hour near-work sessions (at 40 cm), one with and one without a VDU, which were carried out in random sequence on two separate days. Distance visual acuity (monocular/binocular) and subjective refractive error were measured before and immediately after both near-work sessions. MANCOVA analysis showed that VDU work produced a significant myopic shift, -0.10 ± 0.18 D (F1,54 = 5.17, p = 0.03) in distance refractive status. This myopic shift was not found after non-VDU work. There was no significant change in monocular (F1,54 = 0.03, p = 0.86) and binocular visual acuity (F1,54 = 0.22, p = 0.64) after near-work with or without VDU. Emmetropic and low-hyperopic schoolchildren are susceptible to VDU near-work after-effect. Sustained VDU near-work causes significant myopic shift in emmetropic and low-hyperopic 7-year-old children. However, the myopic shift is not accompanied by a reduction in visual acuity.